Preparation of potassium cryolite type scintillator materials

By introducing excess boron into the potassium cryolite molten bath and employing a specific crystal growth method, the problems of inclusions and minor phases in the preparation of potassium cryolite single crystals were solved, resulting in higher preparation yield and better scintillation performance.

CN113174635BActive Publication Date: 2025-01-07LUXIUM SOLUTIONS LLC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202110461201.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2013-04-12
Filing Date
2014-04-11
Publication Date
2025-01-07
Estimated Expiration
2034-04-11

AI Technical Summary

Technical Problem

Existing techniques for preparing potassium cryolite single crystals often result in inclusions and minor phases, leading to low yields and difficulty in approaching the theoretical stoichiometric composition. In particular, the enrichment of Li affects scintillation performance.

Method used

By introducing an excess of boron (2s/r>1) into the molten bath and employing crystal growth methods such as Czeklauski or Bridgman, the composition of the molten bath is controlled to reduce the formation of parasitic phases, approaching or exceeding the stoichiometric composition. Multi-crucible technology is used to ensure the homogeneity of the liquid composition.

Benefits of technology

The proportion of inclusions was significantly reduced, the yield of single crystal preparation was improved, and potassium cryolite closer to the theoretical stoichiometry was obtained, which improved light transmission and energy resolution. In particular, Li-enriched potassium cryolite materials exhibited better scintillation performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113174635B_ABST
    Figure CN113174635B_ABST
Patent Text Reader

Abstract

The present invention relates to the preparation of elvcryolite type scintillator material, in particular to the preparation of a scintillator material having a theoretical composition of A2BC (1‑y) M y X (6‑y) A method for preparing a crystalline scintillator material of a elva cryolite type structure, wherein: A is selected from Cs, Rb, K, Na; B is selected from Li, K, Na; C is selected from rare earth elements, Al, Ga; M is selected from alkaline earth metals; X is selected from F, Cl, Br, I, and y is the atomic fraction of C replaced by M and is in the range of 0 to 0.05, the method comprising crystallization by cooling starting from a molten bath containing r moles of A and s moles of B, the molten bath being in contact with a material containing A and B so that 2s / r is greater than 1. The method has an improved preparation yield. Moreover, the obtained crystals can have a composition closer to stoichiometry and have improved scintillation properties.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the PCT application with a priority date of April 12, 2013, PCT application number PCT / FR2014 / 050893, an application number entering the national phase of 201480020858.2, and an invention name of “Preparation of potassium cryolite type scintillator materials”. Technical Field

[0002] The present invention relates to a method for preparing the elbainite phase (especially single crystal) of rare earth or metal halide with good yield. Background Art

[0003] Scintillator materials are widely used to detect gamma or X-rays and high-energy particles such as alpha particles, neutrons, etc.

[0004] Scintillation is based on the physical principle of converting the energy of photons, incident X- or gamma rays or high-energy particles into light in the visible region or near the visible region. In particular, inorganic scintillators are preferably single-crystalline or polycrystalline. Single crystals allow easier extraction of light due to the absence of in-scattering across grain boundaries, inhomogeneities and other defects present in polycrystalline materials. A good crystal state is necessary because it most effectively determines the scintillation mechanism. The extracted light is then collected by devices known to those skilled in the art as photomultiplier tubes, photodiodes, SiPMs (silicon photomultipliers), APDs (avalanche photodiodes), etc. Polycrystalline scintillators can be prepared from powders that are compacted or sintered or coated with a binder so as to always allow extraction of light. Typically, these non-single-crystalline materials are too opaque beyond a certain thickness and are not sufficient to stop enough incident high-energy particles or photons. Typically, single-crystalline scintillator materials are preferred. The detection of gamma photons, alpha or beta particles, charged particles or neutrons is of major benefit in nuclear medicine, in fundamental physics, in security scanners for baggage (detection gantries), in continuous monitoring of border containers and trucks, in geophysical diagnostic systems in mines and for oil drilling, among other applications. In these applications, it is also generally desirable to be able to distinguish between neutrons and gamma rays, and the scintillation detector should in this case be able to produce a signal with a different fluorescence characteristic depending on the type of ray. WO2005 / 068585 teaches this type of elvryolite scintillator. US8362439 teaches a mixture of elvryolite scintillators.

[0005] The usual method for a person skilled in the art who seeks to prepare a single crystal of elpasolite is to carry out a crystallization starting from a molten bath, the composition of which corresponds to the stoichiometry of the target crystal. Whatever the crystal growth method used, for many complex compositions (three components or even more complex), there is the phenomenon of incompatible melting. The crystallization of the main phase of elpasolite is accompanied by or preceded by the precipitation of a secondary phase, which can appear in the form of inclusions or single-phase regions of undesirable phases. It has now been noted that the crystalline material obtained from these molten baths with complex compositions contains a high proportion of inclusions, or even consists only of parasitic secondary phases. The crystalline material obtained of the single crystal or polycrystalline type can also be referred to as an ingot. In the case of a single crystal made from an incompatible melt, the secondary phase is usually located at the end or periphery of the single crystal material. This secondary phase forms an opaque area that interferes with the single crystal characteristics of the main phase. In certain favorable cases, it is still possible to recover part of the single crystal material by finally cutting away these unusable areas and preserving the transparent single crystal part without inclusions. These inclusions correspond to parasitic phases having a composition different from the composition sought. According to the present invention, a process has been found which reduces the proportion of these impure regions and even eliminates them in certain cases and in this case provides better production yields.

[0006] In addition to obtaining better production yields, the invention also allows obtaining crystals with a composition closer to the theoretical stoichiometry of siliceous stone, even in certain cases enriching it, in particular enriching certain elements, such as Li. The enrichment of Li is advantageous for the detection of neutrons. In most cases, a composition closer to the theoretical stoichiometry manifests itself in better light transmission and, in the case of scintillation, better energy resolution. Moreover, the invention allows the use of the so-called "Czochralski" growth method, which has always been considered by those skilled in the art to be impossible for incompatible melt crystals (in particular most siliceous stone crystals). In Brigman growth, the method according to the invention allows obtaining a higher material yield of usable crystals, i.e. it results in crystal blocks containing fewer parasitic phases for the incompatible melt siliceous stone. Summary of the invention

[0007] The present invention relates to a method for preparing a crystalline scintillator material and to the crystalline scintillator material itself. The present invention relates to a method for preparing a crystalline scintillator material of the elbainite type structure having the following theoretical composition

[0008] A2BC (1-y) M y X (6-y) (1)

[0009] in

[0010] ○ A is selected from Cs, Rb, K, Na

[0011] ○ B is selected from Li, K, Na

[0012] ○ C is selected from rare earth, Al, Ga

[0013] ○ M is selected from alkaline earth elements, in particular Ca, Mg, Sr, Ba

[0014] ○ X is selected from F, Cl, Br, I,

[0015] wherein y represents the atomic fraction (or molar fraction) of substitution of C by M (the elements C and M occupy the same site of the elpasolite) and is in the range of 0 to 0.05 (which means that y can be zero), the method comprising crystallization by cooling starting from a molten bath comprising r moles of A and s moles of B, the molten bath being in contact with a material comprising A and B such that 2s / r is greater than 1.

[0016] The above does not mean that the crystalline scintillator material actually obtained by the method of the present invention has a theoretical stoichiometric composition. They mean that it produces a crystal whose formula would be formula (1) if its composition was actually theoretical (ie stoichiometric).

[0017] The formula of the material actually prepared can be determined from elemental analysis (ICP - Inductively Coupled Plasma - or XRF - X-ray Fluorescence) of each element (except Li in the case of XRF) and by agreeing that the sum of the cations in the formula of elbainite is 4.

[0018] The fact that the ratio 2s / r is higher than 1 represents, within the scope of the invention, an "excess of B" in the molten bath. It is in this sense that the expression "excess of B" can be used within the scope of the present application. This is because the theoretical stoichiometry of elpasolite is such that the ratio of twice the number of moles of B to the number of moles of A is equal to 1. It has now been found that in the crystals actually prepared, this ratio is actually lower than 1, and that by working with a 2s / r of 1, and precisely by increasing the 2s / r ratio in relation to the molten bath, the stoichiometric atomic (or molar) ratio of B to A can be approached or even reached, or even exceeded, in the elpasolite actually prepared.

[0019] Preferably, 2s / r is higher than 1.05, more preferably higher than 1.25 or even higher than 1.5. In particular, 2s / r may be higher than 1.15. In particular, 2s / r may be higher than 1.35. In the case of too great a B excess (too high a 2s / r ratio), parasitic phases may form, also giving rise to harmful inclusions. Preferably, the molar excess of B in the bath (and therefore the 2s / r ratio) is not sufficient to cause the formation of B3C at the start of crystallization. (1-y) M yX6 phase, at least it is low enough to cause the formation as little as possible. Therefore, 2s / r is preferably less than 10 and more preferably less than 5. In particular, 2s / r may be generally less than 3.

[0020] The 2s / r ratio is calculated by the molar amount of A and B introduced into the bath. Elements A and B are introduced in halogenated form. For the case where the bath contains K or Na, considering that these elements can run to the A type site or the B type site, the ratio of these elements running to the A site and the B site can be determined experimentally, so that the 2s / r ratio can be calculated then. In order to determine the ratio of Na and K present at either site, structural studies can be implemented using X-ray diffraction. For this reason, sealed sample bags are used to prevent hydration and destruction of the powder when it comes into contact with ambient air. Because these materials are very strongly hygroscopic. According to the present invention, the excess of Na or K (as B type elements) is therefore determined a posteriori by the precise formula of the finally prepared potassium cryolite by determining the relative percentage of Na or K at the A type site or the B type site. Usually, Na will mainly run to the B type site. For example, if crystallization has been carried out from a bath containing 1.7 mol of CsCl, 1.5 mol of LiCl, 0.5 mol of NaCl and 2 mol of YCl3, and the Na contained in the actually crystallized eluvialite is 80% on B-type sites and 20% on A-type sites, then 0.5 mol of Na in the bath can be decomposed almost into 0.1 mol of ACl-type NaCl and 0.4 mol of BCl-type NaCl. The bath thus contains 1.8 mol of ACl (1.7 mol of CsCl+0.1 mol of NaCl), 1.9 mol of BCl (1.5 mol of LiCl+0.4 mol of NaCl) and 2 mol of YCl3. The 2s / r ratio is thus 2.1.

[0021] The compound carrying A, B, C and M is present in the molten bath as a halide, the halogen of which corresponds to X of formula (1). Several different halogens X can be present in the molten bath if the final crystal must contain different halogens. If t represents the number of moles of C in the molten bath and if u represents the number of moles of M in the molten bath, then preferably the ratio 2(t+u) / r is in the range of 0.8-1.2. Preferably, u / (t+u) is lower than 0.1. In particular, u can be zero.

[0022] The crystalline potassium cryolite obtained by the method according to the present invention can have a true formula that is very close to the theoretical stoichiometry. This true formula can be represented by the following formula:

[0023] A a B b C c M m Xx (2)

[0024] wherein A, B, C, M and X have the meanings given above, and a, b, c, m and x denote the respective atomic fractions of atoms A, B, C, M and X. The atomic ratio 2b / a is in the range of 0.97 to 1.4 (the end values ​​are therefore included in the range), such 2b / a ratios being generally below 1.2.

[0025] The crystals according to the present invention are mainly of the space group The sum of the atomic fractions of the conventional cations (i.e., a+b+c+m) is equal to 4, typically a is in the range of 1.7 to 2.3, b is in the range of 0.8 to 1.2, c is in the range of 0.85 to 1.1, m is in the range of 0 to 0.05, and x is in the range of 5.05 to 6.9.

[0026] In the method according to the invention, the B excess is preferably sufficient so that in the actually prepared potassium cryolite, the ratio of twice the atomic fraction of B-type elements to the atomic fraction of A-type elements (hence the 2b / a ratio in formula (2)) is at least 0.97.

[0027] In formulas (1) and (2), A can be a mixture of several elements selected from Cs, Rb, K and Na. Similarly, B can be a mixture of several elements selected from Li, K or Na. The present invention more particularly relates to the case where B contains Li. In many cases, B is only Li. Similarly, C can be a mixture of several elements selected from rare earths (including Sc and Y), Al and Ga. Similarly, M can be a mixture of several elements selected from alkaline earth elements, in particular a mixture of several elements selected from Ca, Mg, Sr or Ba. In addition, X can be a mixture of several elements selected from F, Cl, Br and I. The present invention more particularly relates to the case where X contains Cl, Br and I.

[0028] The present invention more particularly relates to the case where A comprises Cs, B comprises Li and X comprises Cl or Br. More particular attention is paid to the following two cases: 1) A comprises Cs, B comprises Li, C comprises La and X comprises Br; 2) A comprises Cs, B comprises Li, C comprises Y and X comprises Cl.

[0029] The rare earth is an element of the lanthanide series from La to Lu, or Sc or Y (the latter two elements are similar to the rare earth). The present invention more particularly relates to the case where C contains a rare earth selected from the lanthanide series from La to Lu or Y.

[0030] The sylvite is doped with an activating element that provides or improves its scintillation properties. The activating element is at least a rare earth selected from Ce, Pr, Eu, Tb and Nd. It can be a mixture of activators, especially a mixture of Ce and Pr. The activating element is part of a C-type element. Usually, in sylvite, the activator C'' is present in a lower atomic fraction c'' than another element C' (especially Y) that is also of C type, and the element C' is present in an atomic fraction c'. If C represents a mixture of two elements C' and C'' (especially Y and Ce, respectively), the atomic fraction c of the C-type element is such that c=c'+c''. The atomic fraction c'' of the activating element C'' is such that c'' / (c+m) is higher than 0.00001 and lower than or equal to 0.1, c represents the atomic fraction of element C (which includes all C-type elements, therefore element C'), and m is the atomic fraction of element M. Elements C and M occupy the same site in the crystal lattice of sylvite. The elpasolite may also contain a mixture of activators, in particular a mixture of Ce and Pr. In this case, the elpasolite contains three C-type elements (all on C-type sites): C', C'' and C''' (for example, in particular Y, Ce and Pr, respectively), the last element being present in an atomic fraction c'''. In this case, (c''+c''') / (c+m) is higher than 0.00001 and lower than or equal to 0.1.

[0031] The presence of M in elbainite, especially Sr, modifies the viscosity of the mixture to be melted, the melting temperature, the emissivity of the bath in the infrared and the surface tension of the bath. The presence of M in the crystal, especially Sr, can modify its scintillation properties such as its luminous efficiency and its energy resolution.

[0032] The present invention more particularly relates to scintillator materials of formula (1) and (2) above, wherein B comprises Li, X comprises Cl, Br or I, and C comprises a lanthanide selected from La to Lu, or a rare earth Y, the scintillator material being doped with an activating element for its scintillation effect. The materials of formula (1) and (2) above can in particular be such that B is Li, X is selected from Cl, Br or I, and C is selected from a lanthanide selected from La to Lu, or Y, the scintillator material being doped with an activating element for its scintillation effect. In particular, the material according to the present invention cannot contain fluorine. The scintillator material prepared according to the present invention can have a high light efficiency, in particular measured using a γ excitation of 662 keV. In particular, the light efficiency can be higher than 15000 photons / MeV. LaBr3-rich materials, such as CLLB, can have a light efficiency higher than 25000 photons / MeV.

[0033] The scintillator material prepared according to the present invention can have excellent energy resolution (small full width at half maximum of the scintillation peak). The scintillation can be measured using 137 The scintillator material prepared according to the present invention can have an energy resolution of less than 6%, or even less than 5%, which is calculated using 137 Cs gamma ray source for measurement. The present invention more particularly relates to the case where B contains Li in formula (1) and (2). The present invention more particularly relates to the case where A contains Cs and B contains Li in formula (1) and (2). The present invention more particularly relates to the case where A contains Cs and B contains Li and C contains La in formula (1) and (2). The present invention more particularly relates to the case where A contains Cs, B contains Li, C contains La and X contains Br in formula (1) and (2), in particular when more than 80 mol% of X is Br (80 mol% of X is Br).

[0034] The present invention relates more particularly to the case where in formulae (1) and (2) A comprises Cs, B comprises Li and C comprises Y. The present invention relates more particularly to the case where in formulae (1) and (2) A comprises Cs, B comprises Li, C comprises Y and X comprises Cl, in particular when X is greater than 80 mol% Cl (80 mol% of X is Cl).

[0035] In particular, potassium cryolite may have the following theoretical composition:

[0036] - doped or undoped Cs2LiYCl6, in particular Cs2LiYCl6:Ce, a compound commonly referred to as "CLYC" by those skilled in the art;

[0037] - doped or undoped Cs2LiLaBr6, in particular Cs2LiLaBr6:Ce, a compound commonly referred to as "CLLB" by those skilled in the art;

[0038] - Doped or undoped Cs2LiLaBr 6(1-z) Cl 6z , wherein z is 0 to 1, especially Cs2LiLaBr 6(1-z) Cl 6z :Ce;

[0039] - doped or undoped Cs2LiLaCl6, in particular Cs2LiLaCl6:Ce, a compound commonly referred to as "CLLC" by those skilled in the art;

[0040] - doped or undoped Cs2LiYBr6, in particular Cs2LiYBr6:Ce, a compound commonly referred to as "CLYB" by those skilled in the art;

[0041] - doped or undoped Cs2LiYF6, in particular Cs2LiYF6:Ce, a compound commonly referred to as "CLYF" by those skilled in the art;

[0042] - Doped or undoped Cs 2(1-z) R 2z LiTRX6, especially Cs 2(1-z) R 2z LiTRX6:Ce, where z is 0 to 1 and TR represents rare earth;

[0043] - doped or undoped Rb2LiYX6, in particular Rb2LiYX6:Ce;

[0044] - Doped or undoped Cs 2(1-z) R 2z LiTRI6, wherein z is 0 to 1, especially Cs 2(1-z) R 2z LiTRI6:Ce, TR represents rare earth,

[0045] - Doped or undoped Cs2LiY (1-x) La x Cl6, especially Cs2LiY (1-x) La x Cl6:Ce.

[0046] Therefore, the A2BC having the theoretical composition prepared by the method according to the present invention can be (1-y) M y X (6-y) And has a real A a B b C c M m X x The scintillator material of the elbainite type structure may correspond to one of the following cases:

[0047] - A is Cs, B is Li, C is a mixture of Y and Ce, and X is Cl;

[0048] - A is Cs, B is Li, C is a mixture of La and Ce, and X is Br;

[0049] - A is Cs, B is Li, C is a mixture of Y and Ce, and X is F;

[0050] - A is Cs, B is Li, C is a mixture of La and Ce, and X is Cl;

[0051] - A is a mixture of Cs and Rb, B is Li, C is a mixture of La and Ce, and X is Br;

[0052] - A is Cs, B is Li, C is a mixture of La and Ce, and X is a mixture of Cl and Br;

[0053] - A is Cs, B is Li, C is a mixture of Y and Ce, and X is a mixture of Cl and Br;

[0054] - A is Cs, B is Li, C is a mixture of La, Y and Ce, and X is Cl;

[0055] - A is a mixture of Cs and Na, B is a mixture of Li and Na, C is a mixture of Y and Ce, and X is Cl.

[0056] According to the invention, a significant reduction or even suppression of the formation of parasitic phases is achieved by preparing the crystal from a molten bath having a composition that is offset relative to the composition of the desired final crystal (in the sense that it contains a molar excess of B relative to the theoretical stoichiometry of the crystal). Moreover, the atomic fraction ratio 2b / a (of formula (2)) is closer to the theoretical stoichiometric ratio of 1, or even higher than 1.

[0057] The growth is initiated starting from a molten bath whose composition does not correspond exactly to the stoichiometric composition of elpasolite, nor to the desired final composition of elpasolite. In general, the method according to the invention is of the "auto-flux" type, i.e. the molten bath contains no chemical elements that are not present at all in the crystal. If the liquid around the crystal or reaching it does not have a homogeneous composition, it is considered that for the portion of the liquid that is in direct contact with the crystal, there is an excess of B (i.e. 2s / r>1). In fact, the so-called "multi-crucible" growth technique can be used, according to which at least two crucibles, one inside the other, are present to implement the method according to the invention, as soon as the composition of the liquid in the innermost crucible and in contact with the crystalline material satisfies the conditions of excess of B according to the invention.

[0058] The method according to the invention is usually carried out in a crucible or a closed or even sealed vial. The crucible can be made of graphite with a pyrolytic coating or of glassy carbon. The closed or even sealed vial is usually made of quartz or glassy carbon or platinum.

[0059] According to the invention, the operation is carried out by placing the halogenated raw material in a container (crucible, vial, etc.) under a non-oxidizing atmosphere, then heating it until the raw material melts, then carrying out crystal growth according to the chosen technique (Bridgeman, Czochralski, etc.) and cooling to ambient temperature.

[0060] The present invention can be implemented to produce single crystals by using one of the techniques known to those skilled in the art, such as the Czochralski technique or the Bridgman technique or the Bagdasarov technique (horizontal Bridgman technique) or the Kyropoulos technique or the "Vertical Gradient Freeze" technique (crystallization by controlling the thermal gradient) or the so-called EFG (Edge Feeding Growth) technique or the "continuous feeding" technique involving the use of multiple crucibles, in particular crystal growth in a double crucible (one of the crucibles is located inside the other).

[0061] A single crystal of elliptic cryolite can have a diameter higher than 10 cm 3 , even higher than 100 cm 3 Even if the ingot grown from a single crystal contains inclusions, the inclusion-free single crystal portion may have a volume higher than 10 cm 3 , even higher than 100cm 3 volume.

[0062] In particular, it is remarkable that the method according to the invention can produce a crystalline block whose first 2 / 3 of the volume of the grown single crystal material contains less than 10% by volume of any phase different from the elvryolite phase. In particular, it is remarkable that in the case of a Czochralski type single crystal growth method, the first 2 / 3 of the volume of the grown single crystal material cannot contain any phase different from the elvryolite phase.

[0063] It is also possible to prepare polycrystals using the method according to the invention. For this purpose, it is sufficient to melt the mixture of raw materials and cool the melt obtained (without particular care). Subsequently, the desired size can be obtained by crushing or grinding. Crystalline powder can also be obtained by grinding.

[0064] The raw materials used to produce the molten bath contain the elements that enter the composition of the elvryolite. It can be, for example, a mixture of halides of A, halides of B, halides of C and halides of M. It is then sufficient to feed an excess of B halides (relative to the target stoichiometric composition of the final crystals). For the mixture of raw materials, it can also be a mixture of several halides, at least one of which contains at least two of the elements A, B, C and M. Still here, it is sufficient to feed an excess of halides containing the element B (relative to the target stoichiometric composition).

[0065] Examples of compounds that can be used to form a Li excess according to the present invention are LiCl, Li3YCl6, Cs3Li2Cl5, Cs2Li3Cl5 and Li3LaBr6.

[0066] The method according to the present invention is embodied as a result of controlled cooling of a bath of a molten composition as crystal growth. This molten composition is obtained by melting a compound or a mixture of compounds (this compound or mixture of compounds is referred to as a precursor) as a raw material for producing the desired composition of the desired element in a liquid bath. A single compound having a composition that precisely matches the composition of the desired molten bath can be used. A mixture of halides of different elements entering the desired composition can also be used as a raw material. Therefore, if it is desired to prepare CLYC, the chloride of Cs, the chloride of Li, the chloride of Y, and, if necessary, the chloride of Ce (in the case of Ce doping) can be mixed.

[0067] The B excess according to the invention does not completely enter the final crystalline material, and the B that does not enter this material can be recovered as a by-product after solidification and reused in particular within the scope of the method according to the invention. If the Czochralski single crystal growth method is used, this remaining excess is present in the liquid phase maintained in the crucible. If the Bridgman single crystal growth method is used, this remaining excess is present in the region containing inclusions, which is mainly formed at the end of the method and in any case is a smaller proportion than when no excess is present.

[0068] The excess of B according to the invention allows the composition of the final crystalline material to be brought closer to the perfect stoichiometric composition A2BC (1-y) M y X (6-y) When crystallization is carried out from a bath having a composition that corresponds exactly to the composition of the target elpasolite crystals, the stoichiometric deficiency is about 2 to 3 mol% B. To overcome this deficiency, the present invention proposes to use a B excess, preferably at least 5 mol% B excess (2s / r>1.05).

[0069] For a given potassium cryolite, there is a minimum value of 2s / r in the molten bath for which the first 2 / 3 of the growing volume of the crystallized mass completely (100%) consists of said potassium cryolite. If t is called the number of moles of C in the bath, then the introduction of raw materials in the bath (so that the 2t / r ratio is higher than 1 or even higher than 1.08, even higher than 1.1, even at least 1.2) allows to reduce the minimum value of 2s / r at which the first 2 / 3 of the growing volume completely (100% by volume) consists of said potassium cryolite. For the same volume of potassium cryolite available in the first 2 / 3 of the crystallized mass prepared, the increase in the 2t / r ratio allows to reduce the 2s / r ratio. The increase in the 2t / r ratio can be achieved by introducing compounds in the molten bath, in particular compounds of the B3CX6 type (B, C and X have the meanings given previously), such as Li3LaBr6 or Li3YCl6. This C excess can also be achieved by a greater amount of CX3. However, the use of B3CX6 type compounds allows to achieve an excess of both B and C. This effect of the high 2t / r ratio on the quality of the crystalline mass is particularly pronounced in the case of lysozyme, for which more than 80 mol% of C is La and more than 80 mol% of X is bromine ("LaBr3-enriched" lysozyme). If 2t / r is higher, the yield of perfect crystals is improved, in particular over the first 2 / 3 of the growth volume. In the case of Bridgman growth, the amount of unsuitable material (in particular the adducts) is reduced at the end of the growth. Figure 1 Gray part of c). In the case of Czochralski growth, less material is left in the bath when the growth is finished. Increasing 2t / r even allows to reduce 2s / r, for example to below 1.65.

[0070] For the case of lysolite in which C comprises La, in particular if more than 80 mol % of C is La and in which X comprises Br, in particular if more than 80 mol % of X is bromine, in particular in the case of lysolite of CLLB type, the fact of having at the same time a 2t / r higher than 1, even higher than 1.08, even higher than 1.1, even at least 1.2, accompanied by a 2s / r higher than 1.05, even at least 1.1, allows to obtain 2b / a of at least 1.1, even at least 1.15, even at least 1.2, in particular up to 1.4.

[0071] The argon cryolites of rare earth halides are usually hygroscopic and must be handled in a suitable atmosphere, i.e. dry and neutral or reducing atmosphere (hydrogenated nitrogen, argon, nitrogen, hydrogenated argon) or in vacuum. This also applies to the measurement techniques used, which must be carried out in a suitable atmosphere, especially diffraction measurements. Diffraction measurements carried out in an unsuitable atmosphere (especially ambient air) can completely falsify the measurement. The Bridgman method, which allows crystallization to take place in sealed vials (usually made of quartz or glassy carbon) under vacuum, is advantageous from this point of view, because crystallization is easily achieved in a suitable atmosphere.

[0072] The temperature to which the molten bath is brought to before crystallization depends on the formulation of the bath. Typically, the bath is brought to 400 to 1100° C., depending on the composition, before crystallization. In the context of the single crystal growth method, the cooling rate is typically 0.01 to 5° C. / hour. In the Bridgman method, the translation speed of the crystal is typically 0.01 to 20 mm / h. If it is sought to obtain polycrystals of the elbainite phase, the cooling rate may be much faster, in particular 5 to 200° C. / h. BRIEF DESCRIPTION OF THE DRAWINGS

[0073] Attached Figure 1 represents the crystal blocks taken out of their vials after the growth of Bridgman type crystals. Case a) corresponds to the situation obtained in the prior art, i.e. an unusable crystal block with a high volume fraction, since the crystal block contains many inclusions (grey part), especially at the beginning of the growth, which corresponds to the lower part of the crystal block. When expressing the results, this narrow part of the crystal block is taken into account and is therefore included as the growth volume according to the invention. Case c) corresponds to the situation according to the invention with a high usable single crystal fraction. The grey part at the top corresponds to an undesirable phase. Case b) corresponds to an intermediate situation, the B excess used is lower than the B excess used in c), which has caused a higher inclusion level.

[0074] Attached Figure 2 represents the crystallized mass after Czochralski type crystal growth. The narrow part in the upper area corresponds to the single crystal seed used to initiate this growth. This part is not taken into account when expressing the results. In a), the crystallized mass is completely unusable, because it is completely contaminated with inclusions and corresponds to the prior art, i.e. lacking B excess. In c), the crystallized mass is perfect, without inclusions. The B excess according to the invention has been used. Case b) corresponds to an intermediate case between cases a) and c), with a B excess lower than that used in c). DETAILED DESCRIPTION

[0075] Example

[0076] A powder mixture of raw materials of the halide type of cations to be intercalated into the elpasolite is prepared.

[0077] Single crystals were prepared by crystallization from a molten bath, the composition of which is listed in Table 1. The examples are either according to the invention or comparative examples and in the latter case include the annotation "comparative". The composition of the bath can be expressed in general terms by introducing it in the form of the sum of stoichiometric amounts of eluvialite and an excess of one or more compounds (including B). In the table, BG indicates that a Bridgman type growth has been carried out and CZ indicates that a Czochralski type growth has been carried out. In the case of Example 8, the sodium was able to move to the sites of Cs or Li, and it was noted a posteriori that in the final crystal, the proportion of Na on the Li sites was 89% and that on the Cs sites was 11%. This is why, for 2 mol of Cs introduced in the bath, the amount of A in the bath is 2 (for Cs) + 0.074 (for 11% of 0.67 mol of Na) or 2.074 mol. The amount of B in the bath is 1 (for Li) + 0.596 (for 89% of 0.67 mol of Na) or 1.596 mol. Here the 2s / r ratio is therefore (2×1.596) / 2.074=1.54.

[0078] In the case of CZ type growth, not all of the used bath is converted into crystalline block material, which is inherent to this technology. In Bridgman crystallization, on the contrary, all of the used bath has solidified into a crystalline block. In the last column of Table 1, the percentage of single crystals that are really usable in the first 2 / 3 of the growth of the solidified crystalline block is given. In CZ growth it is therefore not about the percentage of material used in the bath. In Bridgman growth, on the contrary, it is also about the percentage of material used in the bath. Examples 20, 21, 22, 24 show that in the case of CLLB, the high 2s / r ratio in the bath leads to a 2b / a significantly higher than 1 in elbainite.

[0079]

[0080]

[0081]

[0082] Table 1 .

[0083] Table 2 gives the scintillation properties of some of the crystals described in Table 1. The relative optical efficiency (LO column for "Optical efficiency"), measured using 662 keV gamma excitation, and the energy resolution (full width at half maximum of the scintillation peak) are indicated here. The scintillation has been measured using 137The implementation was carried out with a Cs type gamma-ray source, a photomultiplier and a standard measuring system. The values ​​obtained are comparable to each other because they are determined using a determined sample geometry and using the same measuring tools. The lower the value of the energy resolution, the better it is. The light efficiency is preferably as high as possible. For CLYC type crystals, the light efficiency has been expressed relative to the light efficiency of Example 1 (arbitrarily evaluated as a LO of 1). For CLLB type crystals, the light efficiency has been expressed relative to the light efficiency of Example 11 (arbitrarily evaluated as a LO of 1).

[0084] Relative LO Energy resolution CLYC Example 1 (reference) 1 6.19% CLYC Example 4 1.15 4.61% CLYC Example 5 1.28 5.15% CLYC Example 7 1.20 4.67% CLLB Example 11 (reference) 1 8.73% CLLB Example 12 1.20 4.14%

[0085] Table 2 .

[0086] Figure 1 a) and 1c) show vials after Bridgman type crystal growth according to the examples. Examples 1, 2 and 15 produced Figure 1 Examples 5, 6, 7, 8, 10, 13, 14 and 17 produced crystal blocks of the type described in a). Figure 1 c). For Examples 5, 6, 7, 8, 10, 13, 14, 17, the first 2 / 3 of the grown volume of the single crystal material contained less than 10% by volume of a phase different from that of elvalcite. In these particular cases, the volume of the impure phase was 0%.

[0087] In the case of Examples 15 and 16, it was shown that the first 2 / 3 volume of phases other than the elbainite phase could be reduced from 24% to 8% with the aid of the invention. Example 16 thus produced Figure 1 The first 2 / 3 of the volume of the grown bulk or single crystal material of type b) contains less than 10% by volume but more than 0% by volume of a phase different from that of elbainite.

[0088] Figure 2 a) and 2c) represent the crystal blocks after Czochralski type crystal growth according to the examples. Figure 2 Examples 4, 9, 12, 18 and 19 were produced on the adjacent Figure 2 For these Examples 4, 9 and 12, 18 and 19, 100% of the grown volume of single-crystalline material does not contain a phase different from that of elpasolite.

[0089] It is clearly seen that the embodiments according to the invention using excess B (or 2s / r>1) lead to much fewer inclusions and thus better single crystal production yields. They also produce better scintillation performance.

[0090] In the case of Examples 5, 6, 19, 20, 21, 22, 24, 25, 26, 27 and 28, 2t / r in the bath was higher than 1 and 2s / r in the bath was higher than 1.08. In these cases, depending on its type, Figure 1 c or 2c, increasing the yield of perfect crystals. In the case of Bridgman growth, it is the Figure 1 The gray part of c is reduced. In the case of Czochralski growth, it is the amount of material remaining in the bath that is reduced. In the case of Examples 7 and 27, the mass of the parasitic phase at the end of the growth (attached Figure 1 c) relative to the total mass of material introduced into the Bridgman vial. It is observed that this percentage in the case of Example 27 (10%) is significantly lower than that of Example 7 (17.9%). The material yield is much higher in the case of Example 27 than in Example 7.

Claims

1. Used to prepare A2BC with theoretical composition (1-y) M y X (6-y) Method for producing a crystalline scintillator material of the potassium cryolite type structure, in -A is selected from Cs, Rb and K, -B is selected from Li and Na, and includes Li, -C is selected from rare earth elements or Y, -M is selected from alkaline earth metals, -X is selected from Cl, Br, I, and contains at least one of Cl or Br, y represents the atomic fraction of C replaced by M and is in the range of 0 to 0.05, the method comprising its crystallization by cooling starting from a molten bath comprising r moles of A and s moles of B, characterized in that the crystalline scintillator material is doped with an activating element for its scintillation action, the molten bath being in contact with the crystalline scintillator material comprising A and B such that 2s / r is greater than 1.05, and 2t / r is 1 or higher, t representing the number of moles of C in the bath, wherein the first 2 / 3 of the growing volume of the crystalline material contains less than 10% by volume of a phase different from that of elvalcite; and The obtained crystal scintillator has the true formula A a B b C c M m X x , wherein A, B, C, M and X have the above definitions, and a, b, c, m and x represent the respective atomic fractions of A, B, C, M and X, and the ratio 2b / a is in the range of 0.97 to 1.

4.

2. The method according to claim 1, characterized in that 2s / r is higher than 1.

15.

3. The method according to claim 1, characterized in that 2s / r is higher than 1.

25.

4. The method according to claim 1, characterized in that 2s / r is higher than 1.

35.

5. The method according to claim 1, characterized in that 2s / r is higher than 1.

5.

6. The process according to claim 1, characterized in that 2s / r is less than 10.

7. The method according to claim 1, characterized in that 2s / r is less than 3.

8. The method according to claim 1, characterized in that M is selected from Ca, Mg, Sr or Ba.

9. A method according to claim 1, characterized in that C contains at least one activated rare earth element chosen from Ce, Pr, Eu, Tb and Nd, whose atomic fraction is such that the ratio of its atomic fraction to the sum of the atomic fractions of the elements C and M in the crystalline material is higher than 0.00001 and lower than or equal to 0.

1.

10. The method according to claim 1, characterized in that 2s / r is not sufficient to cause the formation of B3C at the beginning of crystallization. (1-y) M y X6 phase.

11. The process according to claim 1, characterized in that B is Li.

12. The method according to claim 1, characterized in that 2t / r is greater than 1.

13. The method according to claim 1, characterized in that the rare earth element comprises an element of the lanthanide series from La to Lu, or Y.

14. The process according to claim 1, characterized in that A comprises Cs and B comprises Li.

15. The method according to claim 14, characterized in that C comprises La and X comprises Br.

16. A process according to claim 15, characterised in that more than 80 mol % of C are La and more than 80 mol % of X are bromine.

17. The method according to claim 14, characterized in that C comprises Y and X comprises Cl.

18. Process according to claim 17, characterised in that more than 80 mol % of C are Y and more than 80 mol % of X are Cl.

19. The process according to claim 1, characterized in that 2t / r is higher than 1.08, t being the number of moles of C in the bath.

20. The process according to claim 19, characterized in that 2t / r is higher than 1.2, t being the number of moles of C in the bath.

21. A process according to claim 19, characterised in that 2t / r is higher than 1.1, t being the number of moles of C in the bath, C comprising La, and X comprising Br, and 2s / r being at least 1.

1.

22. The method according to claim 21, characterized in that 2t / r is at least 1.

2.

23. A process according to claim 21, characterised in that more than 80 mol % of the C is La.

24. The process according to claim 21, characterized in that more than 80 mol % of X is bromine.

25. A method according to claim 1, characterised in that it is a single crystal growth method.

26. A method according to claim 25, characterized in that the crystallization is of the Czochralski type and in that the first 2 / 3 of the grown volume of the single-crystalline material does not contain a phase different from that of elpasolite.

27. A method according to claim 26, characterised in that the crystalline material is melted incompatiblely.

28. Has theoretical composition A2BC (1-y) M y X (6-y) And has true form A a B b C c M m X x A crystalline scintillator material of a eluvialite type structure, wherein the crystalline scintillator material is doped with an activating element for its scintillation effect, wherein -A is selected from Cs, Rb, K, -B is selected from Li and Na, and includes Li, -C is selected from rare earth elements or Y, -M is selected from alkaline earth metals, -X is selected from Cl, Br, I, and contains at least one of Cl or Br, y represents the atomic fraction of C replaced by M, and in the range of 0 to 0.05, a, b, c, m and x represent the respective atomic fractions of A, B, C, M and X, and the ratio 2b / a is in the range of 0.97 to 1.4, wherein the first 2 / 3 of the growing volume of the crystalline material contains less than 10% by volume of a phase different from that of elvasolite.

29. Material according to claim 28, characterized in that C contains at least one activated rare earth element chosen from Ce, Pr, Eu, Tb and Nd, whose atomic fraction is such that the ratio of its atomic fraction to the sum of the atomic fractions of the elements C and M is higher than 0.00001 and lower than or equal to 0.

1.

30. A material according to claim 28, characterised in that A comprises Cs.

31. The material according to claim 28, characterized in that C comprises La and X comprises Br.

32. A material according to claim 28, characterised in that more than 80 mol % of C is La and more than 80 mol % of X is Br.

33. A material according to claim 28, characterised in that C comprises Y and X comprises Cl.

34. A material according to claim 28, characterised in that more than 80 mol % of C are Y and more than 80 mol % of X are Cl.

35. The material according to claim 28, characterized in that the crystalline scintillator material is a single crystal.

36. The material according to claim 28, characterized in that C contains a rare earth element selected from the lanthanides from La to Lu or Y.

37. A material according to claim 28, characterized in that A is Cs, B is Li, C is a mixture of Y and Ce, and X is Cl.

38. A material according to claim 28, characterized in that A is Cs, B is Li, C is a mixture of La and Ce, and X is Br.

39. A material according to claim 28, characterized in that A is Cs, B is Li, C is a mixture of La and Ce, and X is Cl.

40. A material according to claim 28, characterized in that A is a mixture of Cs and Rb, B is Li, C is a mixture of La and Ce, and X is Br.

41. A material according to claim 28, characterized in that A is Cs, B is Li, C is a mixture of La and Ce, and X is a mixture of Cl and Br.

42. A material according to claim 28, characterized in that A is Cs, B is Li, C is a mixture of Y and Ce, and X is a mixture of Cl and Br.

43. A material according to claim 28, characterized in that A is Cs, B is Li, C is a mixture of La, Y and Ce, and X is Cl.

44. A material according to claim 28, characterized in that A is a mixture of Cs and Na, B is a mixture of Li and Na, C is a mixture of Y and Ce, and X is Cl.

45. A material according to claim 28, characterised in that the 2b / a ratio is in the range of 1.1 to 1.

4.

46. ​​The material according to claim 28, characterized in that the crystalline material is non-compatible melting.

47. A material according to claim 28, characterised in that it has a scintillation energy resolution of less than 6%, even less than 5%, using a 662 keV 137 Cs gamma-ray source for measurement.

48. The material according to claim 28, characterized in that the first 2 / 3 of the growth volume of the material does not contain a phase different from that of elpasolite.

Citation Information

Patent Citations

  • Mixed cesium sodium and lithium halide scintillator compositions

    US8362439B1

  • Bright and fast neutron scintillators

    WO2005068585A1

  • Scintillation compound including a rare earth element and a process of forming the same

    WO2013041251A2